Polímeros biorreabsorvíveis como substrato para cultura de células e engenharia tecidual - Santos Jr., Arnaldo R. [UNESP]; Wada, Maria Lucia F. (My University, 2007)
Polymerie biomaterials are used as replacements for damaged tissue or/and for stimulating its regeneration. A class of polymeric biomaterials is the bioreabsorbable ones, which degrade in vitro as well as in vivo. They are used in tissues that need a temporary support for its tissue regeneration. Among the several bioabsorbable polymers are included α-hydroxy acids, in different forms of poly(lactic acid) (PLA), such as the poly(L-lactic acid) (PLLA), poly(D-lactic acid) (PDLA), poly(DL-lactic acid) (PDLLA), in addition to poly(glycolic acid) (PGA) and poly(caprolactone) (PCL). These polymers are well-known because their decomposition products are eliminated from the body via metabolic routes and due to their good biocompatibility. Many results show that the different PLA based substrates do not present toxicity, once the cells could differentiate over the different polymers, which was demonstrated by the production of extracellular matrix components by many cell types. In this work, we reviewed the employment of α-hydroxy acid, with emphasis on different forms of PLA scaffolds used as cell culture substrates and their applications.
Bioreabsorbable polymers for cell culture substrate and tissue engineering
Keywords: Bioreabsorbable polymers; Cell culture; Tissue engineering